2005
DOI: 10.1093/carcin/bgi298
|View full text |Cite
|
Sign up to set email alerts
|

Signalling cell cycle arrest and cell death through the MMR System

Abstract: Loss of DNA mismatch repair (MMR) in mammalian cells, as well as having a causative role in cancer, has been linked to resistance to certain DNA damaging agents including clinically important cytotoxic chemotherapeutics. MMR-deficient cells exhibit defects in G2/M cell cycle arrest and cell killing when treated with these agents. MMR-dependent cell cycle arrest occurs, at least for low doses of alkylating agents, only after the second S-phase following DNA alkylation, suggesting that two rounds of DNA replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
143
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 129 publications
11
143
0
Order By: Relevance
“…The presence of wt MLH1 (OVCAR3) or a re-expression in an MLH1-defective A2780 variant did not significantly alter the proliferation rate in cisplatin response, but significantly increased sensitivity to 6-TG, a chemotherapeutic purine nucleoside analogue, the primary mechanism of action of which is dependent on the presence of a functional DNA MMR system (Hawn et al, 1995;Buermeyer et al, 1999;Yan et al, 2003) consistent with earlier reports Branch et al, 2000). However, both 6-TG and cisplatin induced an MLH1-dependent apoptosis and arrest in the G2/M phase of cell cycle (our unpublished observations), consistent with earlier reports in OVCAR3 Kolfschoten et al, 2002) (O'Brien andBrown, 2006). The MLH1 proteolysis in cells undergoing apoptosis correlated with the increased expression of active forms of caspase-3 and -9.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The presence of wt MLH1 (OVCAR3) or a re-expression in an MLH1-defective A2780 variant did not significantly alter the proliferation rate in cisplatin response, but significantly increased sensitivity to 6-TG, a chemotherapeutic purine nucleoside analogue, the primary mechanism of action of which is dependent on the presence of a functional DNA MMR system (Hawn et al, 1995;Buermeyer et al, 1999;Yan et al, 2003) consistent with earlier reports Branch et al, 2000). However, both 6-TG and cisplatin induced an MLH1-dependent apoptosis and arrest in the G2/M phase of cell cycle (our unpublished observations), consistent with earlier reports in OVCAR3 Kolfschoten et al, 2002) (O'Brien andBrown, 2006). The MLH1 proteolysis in cells undergoing apoptosis correlated with the increased expression of active forms of caspase-3 and -9.…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies in vitro (Aebi et al, 1996;Brown et al, 1997;Fink et al, 1998b;O'Brien and Brown, 2006) have reported a correlation between MMR deficiency and platinum resistance. Indeed, studies link MMR deficiency with reduced CR to platinumbased chemotherapy (Fink et al, 1998b;Strathdee et al, 2001;Gifford et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSH2 binds to CHK1 and CHK2 both in vivo and in vitro [17]. ATM (ataxia-telangiectasia-mutated kinase), CHK1 and CHK2 have all been implicated in triggering the G2/M checkpoint response, and MMR genes are presumed to play a role in the G2/M cell cycle checkpoint [18]. Campregher et al [19] used an in vitro co-culture model that mimicked intestinal inflammation in ulcerative colitis, in which the activated neutrophils caused an accumulation of target cells in G2/M, which was consistent with the installation of a DNA-damage checkpoint.…”
Section: Discussionmentioning
confidence: 99%